Prospective study of spectrum, clinico-epidemiology, profile complication and outcome of pesticide poisoning in children - Rao, K. Visweswara; Ramesh, G.; Acharya, Anand (International Journal of Contemporary Pediatrics, 2019)
Background: Konaseema region of Andhra Pradesh is a rural area having well irrigated lands and rice fields. Agriculture is the major some of income, and pesticide use is high. As per one report of deccan chronicle (a daily newspaper) Andhra Pradesh and Telangana accounts for 24% share of pesticide consumption in the country. Pediatric pesticide poisoning is under reported in India as well. In this background resent study has been designed to study clinic-epidemiology, profile, complication and treatment outcome of pesticide poisoning in Konaseema region of Andhra Pradesh. Methods: In present study clinico-epidemiology, clinical profile, complication and outcome of the patient admitted in the Department of Emergency medicine and Paediatric were evaluated over a period of 12years. Results: Most of the children were above 5years of age that is 74.0% (n=40), rest were below 5years of age. Male children out numbered female children and accounted for 77.78% (n=42). Accidental poisoning was more than suicidal poisoning that is 94.59% of the patients. 9.35% patient (n=5) developed respiratory failure and required ventilator support. Non-carcinogenic pulmonary edema was present in 8 (14.81%) patients. Four patients have atropine toxicity, electrolyte in balance was found in 7.4% (n=4) patients. Acute kidney injury was present in two patients, 5.5% (n=3) patients developed cardiac arrhythmia. Conclusions: Chlorpyrifos was common agent which is responsible for poisoning most common complication in our patients were respiratory complications which required ventilatory support. Lack of information, improper disposal of container, non-existence of training and regulation is supported to the cause of accidental exposure of pesticide to paediatric patients.